Supervised Credit, Government Strategies and Green Development: Evidence from China - Zhang, Bingbing (Problemy Ekorozwoju, 2023)
This study examines the relationship between supervised credit (SC), government strategies, and green development (GD) utilizing the instrumental variable two-stage least squares (IV-2SLS) and spatial econometric model and panel data from 30 provinces and cities in China from 2006 to 2020. The study reached the following main results. First, untrustworthy punishment and trustworthy incentives promote the environmental protection through optimal allocation of supervised resources, which can be positively regulated by the government transformation. Second, beggar-thy-neighbor and free rider can be found in government environmental SC. Strengthening punishment in neighboring regions will have a negative effect on the local GD, whereas increasing incentives will have the opposite effect. Third, strategic interactions among various governmental sections have varying effects on GD. The eastern regions implement difference-based promotion for trustworthy incentives and ineffective imitation for untrustworthy punishment. The central and western regions, on the other hand, use ineffective imitation for trustworthy incentives and inhibiting imitation for untrustworthy punishment, the eastern regions implement ineffective imitation and the central and western regions execute inhibiting imitation. Finally, when R&D investment exceeds a certain threshold, but the industrial structure is lower, the untrustworthy punishment can play its promoting role; otherwise, the trustworthy incentives will turn over. The study findings reveal the unique mechanism of SC and provides new impetus regional policymakers to promote sustainable GD.